Strategic Business Management and Its Role in the Formalization of Micro and Small Enterprises in Emerging Economies - Uldarico Inocencio Aguado-Riveros; Sonia Luz Barzola-Inga; Carlos Antonio Adauto-Justo; Diana Pariona-Amaya; Luis Enrique Espinoza-Quispe; Luis Alberto Poma-Lagos; Vicente González-Prida; Javier Amador Navarro-Veliz (World)
This study explores the connection between business management and the formalization of micro and small businesses (MSEs) in a particular developing economy environment. The main objective is to identify the business management factors that influence the business registration and compliance processes of these enterprises. This study uniquely contributes to the literature by empirically identifying and testing the specific business management factors that influence MSE formalization in an emerging economy, using a quantitative, data-driven approach. The research design utilizes quantitative methods and non-experimental and correlational elements while surveying 186 informal entrepreneurs from a total population of 361. The analysis used SPSS software version 25 on Likert-type scale survey data to identify relationships between investigated variables. The results demonstrate a weak positive association between business management and MSE formalization through their r = 0.386 Spearman correlation coefficient, which reaches statistical significance at a p-value of 0.000. In addition, positive correlations were identified between resource availability and accessibility and service quality with formalization, whereas acceptability and adaptability did not show a significant relationship (r = 0.256, p = 0.000; r = 0.359, p = 0.000). The formalization of MSEs depends on proper business management; however, a broader contextual approach is required to meet specific demands in local areas such as the study area. These findings suggest the implementation of integrated policies that improve the availability, accessibility, and quality of resources and services offered to MSEs.